Phospholipid biosynthesis genes and susceptibility to obesity: analysis of expression and polymorphisms. - Neeraj K Sharma; Kurt A Langberg; Ashis K Mondal; Swapan K Das (PLoS ONE, 2013)
Recent studies have identified links between phospholipid composition and altered cellular functions in animal models of obesity, but the involvement of phospholipid biosynthesis genes in human obesity are not well understood. We analyzed the transcript of four phospholipid biosynthesis genes in adipose and muscle from 170 subjects. We examined publicly available genome-wide association data from the GIANT and MAGIC cohorts to investigate the association of SNPs in these genes with obesity and glucose homeostasis traits, respectively. Trait-associated SNPs were genotyped to evaluate their roles in regulating expression in adipose. In adipose tissue, expression of PEMT, PCYT1A, and PTDSS2 were positively correlated and PCYT2 was negatively correlated with percent fat mass and body mass index (BMI). Among the polymorphisms in these genes, SNP rs4646404 in PEMT showed the strongest association (p = 3.07E-06) with waist-to-hip ratio (WHR) adjusted for BMI. The WHR-associated intronic SNP rs4646343 in the PEMT gene showed the strongest association with its expression in adipose. Allele "C" of this SNP was associated with higher WHR (p = 2.47E-05) and with higher expression (p = 4.10E-04). Our study shows that the expression of PEMT gene is high in obese insulin-resistant subjects. Intronic cis-regulatory polymorphisms may increase the genetic risk of obesity by modulating PEMT expression.